2016
DOI: 10.1007/s13277-016-4883-7
|View full text |Cite
|
Sign up to set email alerts
|

Differential blood-based diagnosis between benign prostatic hyperplasia and prostate cancer: miRNA as source for biomarkers independent of PSA level, Gleason score, or TNM status

Abstract: Since the benefit of prostate-specific antigen (PSA) screening remains controversial, new non-invasive biomarkers for prostate carcinoma (PCa) are still required. There is evidence that microRNAs (miRNAs) in whole peripheral blood can separate patients with localized prostate cancer from healthy individuals. However, the potential of blood-based miRNAs for the differential diagnosis of PCa and benign prostatic hyperplasia (BPH) has not been tested. We compared the miRNome from blood of PCa and BPH patients and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
33
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 49 publications
0
33
1
Order By: Relevance
“…In another study, miR-21 in patients’ plasma was also found as a miRNA predicting aggressiveness of prostate cancer [ 35 ]. miR-221-5p and miR-708-3p were confirmed to be downregulated in blood of prostate cancer patients compared with benign prostate hyperplasia (BPH) patients by quantitative real-time PCR (qRT-PCR) [ 36 ]. Ambs et al reported that miR-106b and miR-32 were upregulated in prostate cancer tissues [ 37 ].…”
Section: Expressions Of Mirnas In Prostate Cancer Tissuementioning
confidence: 99%
“…In another study, miR-21 in patients’ plasma was also found as a miRNA predicting aggressiveness of prostate cancer [ 35 ]. miR-221-5p and miR-708-3p were confirmed to be downregulated in blood of prostate cancer patients compared with benign prostate hyperplasia (BPH) patients by quantitative real-time PCR (qRT-PCR) [ 36 ]. Ambs et al reported that miR-106b and miR-32 were upregulated in prostate cancer tissues [ 37 ].…”
Section: Expressions Of Mirnas In Prostate Cancer Tissuementioning
confidence: 99%
“…Oncogenic processes may highly influence cellular glycosylation process and PSA has carbohydrate content so it is predicted that glycosylation involves alteration of gene expression and activity of glycosyltransferases 16. One more approach of early detection of PCa using non-invasive way is to measure non-coding RNA, miRNA level in patients' blood 28. It has been shown that in PCa and BPH patients, seven miRNAs such as miR-675 levels were significantly altered in cancer and non-cancer groups 28.…”
Section: Discussionmentioning
confidence: 99%
“…One more approach of early detection of PCa using non-invasive way is to measure non-coding RNA, miRNA level in patients' blood 28. It has been shown that in PCa and BPH patients, seven miRNAs such as miR-675 levels were significantly altered in cancer and non-cancer groups 28.…”
Section: Discussionmentioning
confidence: 99%
“…Since the benefit of prostate-specific antigen (PSA) screening remains controversial, new non-invasive biomarkers for prostate carcinoma (PCa) are still required, new evidence showed that microRNAs (miRNAs) in whole peripheral blood can separate patients with localized prostate cancer from healthy individuals [15].…”
Section: Discussionmentioning
confidence: 99%